Mouse Lipocalins (MUP, OBP, LCN) Are Co-expressed in Tissues Involved in Chemical Communication - Stopková, Romana; Vinkler, David; Kuntová, Barbora; Šedo, Ondrej; Albrecht, Tomáš; Suchan, Jan; Dvořáková-Hortová, Kateřina; Zdráhal, Zbyněk; Stopka, Pavel (Frontiers in Ecology and Evolution, 2016)
Chemical communication is mediated by signal production and signal perception and in house mice (Mus musculus), both processes involve lipocalin proteins (OBP, MUP, LCN) that transport volatiles and protect them in tissues where they are produced. However, potential roles of lacrimal, nasal, and salivary lipocalins are still not well known. We aimed to determine the expression of the recently described family of odorant binding proteins (Obp), along with major urinary proteins (Mup) across different tissues in wild mice (Mus musculus) to assess the importance of these proteins based on their quantity in particular expression sites. We performed qPCR analysis of selected Mup, Lcn, Obp genes, and predicted Obp members to study their expression in selected tissues. We identified new members of the mouse odorant binding protein gene family in two subspecies, M. m. musculus and M. m. domesticus. We show that Mup4 and Mup5 from the phylogenetically older group-A are co-expressed with Obps in orofacial tissues. We also identified a sexually dimorphic pattern of female-biased Obp7 and male-biased Mup4 expression in lacrimal glands. OBPs, MUPs, and LCNs are produced in parallel, which may function to widen the spectrum of bound ligands, potentially including the degradation products of olfactory signals and/or toxic compounds. Moreover, our study demonstrates that several pheromone transporters from the lipocalin family are co-expressed in the nasal and lacrimal tissues of mice with the newly detected OBPs that further expand the already diverse mouse lipocalin family.